Penentuan Rute Optimal Untuk Jasa Pengiriman Barang Menggunakan Algoritma Genetika - Gatra Cahya Ramadhan; Pratama Bagus W; Yesy Diah Rosita (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
In the delivery process there is a problem commonly known as the Travelling Salesman Problem (TSP), therefore a program is needed that can minimize shipping costs and find a quick route to maximize the profits obtained. Then, set up alternative routes and optimum routes so that the problem can be solved. The purpose of this research is to determine the route or route and the minimum distance search results in goods delivery services using the method of genetic algorithms. Using 27 randomly selected data points from four sub-districts in the Mojokerto district, Clustering data is divided into three clusters and tested using MATLAB software. Using a crossover probability of 0.6, the probability of mutation is 0.4, and the total population is 27. The results of the test in finding the optimal route and the fast track are in the second cluster with a distance of 20 km and the optimal route of 5-8-7-1-9-4 -10-3-6-2-5, i.e., Dsn. Mojoroto, Banjartanggul, Dsn. Sumber Bendo, Perum Mojo Asri, Wonokoyo, Dsn. Trawas, Wonokusumo, Dsn. Pecuk, Dsn. Resik Bulu, Damarsi, Etc. Mojoroto From the optimal route generated in this study, it is expected that the shipping service can get the optimal route to speed up the delivery of goods.